2020
DOI: 10.1016/j.ijso.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral treatment failure among HIV-positive adults taking first-line therapy and associated risk factors at Adigrat General hospital, Adigart, Ethiopia 2019: A cross sectional study

Abstract: Background: Human Immunodeficiency Virus (HIV) is a major public health problem globally. Highly active antiretroviral therapy (HAART) has led to profound reduction in the incidence of mortality. However, effective treatment is challenged by the treatment failure. Anti-Retroviral Treatment (ART) Failure may predispose patients to new or recurrent clinical condition. Objective: This study was designed to assess virological and immunological failure of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The finding of this study is lower than the finding from Adigrat, in which immunologic and virologic overall prevalence of treatment failure was 27.48%. 29 The difference is that in the study done by Demsie et al, the prevalence report was both cumulative overall result of both immunologic and virologic ART treatment failure. Similarly, it is lower than that of the study conducted by Gesesew et al in South West Ethiopia which was 25.1% 30 and Lenjiso et al’s study in Dire Dawa which was 22.7%.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The finding of this study is lower than the finding from Adigrat, in which immunologic and virologic overall prevalence of treatment failure was 27.48%. 29 The difference is that in the study done by Demsie et al, the prevalence report was both cumulative overall result of both immunologic and virologic ART treatment failure. Similarly, it is lower than that of the study conducted by Gesesew et al in South West Ethiopia which was 25.1% 30 and Lenjiso et al’s study in Dire Dawa which was 22.7%.…”
Section: Discussionmentioning
confidence: 87%
“…This is similar to a finding of an Adigrat study in which WHO stages III/IV were significantly associated with treatment failure in multivariable analysis. 29 Likewise, in Huang et al’s study in China, patients with WHO clinical stage IV were 4.16 times more likely when compared with those with stage I. 27 The severe AIDS symptoms which have been categorized under WHO stage III and IV were the predictors for ART regimen treatment failure.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is difficult to compare within the literature of virologic outcomes in YLWH; we are not aware of any study that reports this kind of association. However, the finding is supported by an investigation from Ethiopia involving adults living with HIV [ 57 ]. Living in a rural area could be an indirect marker of treatment interruption because of reasons such as difficulties in accessing HIV treatment services.…”
Section: Discussionmentioning
confidence: 75%
“…The high transport costs may be a deterrent to YLWH in seeking routine HIV care, especially if the financial obligation lies with them. Treatment interruption is significantly associated with poor virological and immunological outcomes [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified poor ART adherence, prolonged ART use, suboptimal ART regimens, tuberculosis (TB) co-infection, treatment interruption, opportunistic infections (OIs), rural residency, advanced WHO stage, and low baseline CD4 count as factors associated with an increased risk of HIV VTF [8][9][10][11][12][13][14]. Adherence to ART has been shown to be one of the most important predictors of virologic success and preventing disease progression [15].…”
Section: Introductionmentioning
confidence: 99%